Comparative Assessment of Trap Charges Effect on Triple Hybrid Metal Gate Dielectric Modulated Junctionless Gate All Around Nanowire FET-Based Biosensor - Mekonnen Getnet Yirak; Rishu Chaujar (Advances in Condensed Matter Physics)
This work investigates how interface trap charges (ITCs) affect the performance of biosensors made from junctionless nanowire field-effect transistors (NWFETs) with triple hybrid metal gate dielectric modulated gates. The subthreshold sensitivity of double and triple metal gate silicon NWFET biosensors was investigated using the SILVACO ATLAS-TCAD simulation tool, emphasizing the impacts of positive and negative ITCs. Simulations examined the impact of uniformly immobilized biomolecules within the nanogap cavity region and evaluated key electrical characteristics, such as transconductance, switching ratio, drain current, and threshold voltage, under trap charges of ±5×1012 cm−2 at the SiO2–silicon interface. Results showed that the triple hybrid metal gate device achieved an 184% improvement in threshold voltage shift compared to the double gate device when negative trap charges were present. The findings imply that integrating negative ITCs enhances the biosensor’s performance and accuracy, emphasizing its importance in device modeling and design optimization.